(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Today we live in a world which is be best described by the VUCA (Vulnerability, Uncertainty, Complexity and Ambiguity) factor. In such a world, with growing level of uncertainties, personal financial planning is of paramount importance. A comprehensive financial plan encompassing all the crucial aspects of personal finance: savings, insurance, investment, retirement, taxation and estate, would not only prepare one for ‘rainy days’ but also ensure fulfillment of various short and long term financial goals. Moreover, at present times, with the onset of the novel corona virus, people around the globe have faced economic insecurity and liquidity crunch. In order to survive such difficult times, personal financial planning is not only a good proposition but has become a basic requirement. The paper attempts to highlight the level of financial planning and financial wellbeing, along with the reasons and challenges faced by respondents while planning. In addition to this, the researcher attempts to determine the association between financial planning and financial wellbeing.